1989
DOI: 10.1038/ki.1989.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy intake on nutritional status in maintenance hemodialysis patients

Abstract: Although maintenance hemodialysis (MHD) patients are often wasted, little is known about their dietary energy needs. We studied four men and two women in a clinical research center while they received diets providing 45, 35 and 25 kcal/kg desirable body weight/day; diets were fed, in random order, for 21 to 23 days each. Protein intake, 1.13 +/- 0.02 (SEM) g protein/kg/day, was similar with all three diets. Body weight rose with 45 and 35 kcal/kg/day (P less than 0.05) and fell with 25 kcal/kg/day (P less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
65
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 27 publications
2
65
0
3
Order By: Relevance
“…The energy intake of our patients, of 23 to 25 kcal kg -1 day -1 , was far below the recommended amount for patients on hemodialysis (29), as systematically observed in many studies (1,6,7). Anorexia of chronic renal failure may be implicated in this low energy intake and may be related to the malnutrition of these patients (30).…”
Section: Discussionmentioning
confidence: 88%
“…The energy intake of our patients, of 23 to 25 kcal kg -1 day -1 , was far below the recommended amount for patients on hemodialysis (29), as systematically observed in many studies (1,6,7). Anorexia of chronic renal failure may be implicated in this low energy intake and may be related to the malnutrition of these patients (30).…”
Section: Discussionmentioning
confidence: 88%
“…15 Protein intake values below the recommended ones are in accordance with the findings of several other studies, 20,24,[26][27][28][29] suggesting a negative nitrogen balance, which jeopardizes the nutritional status of HD patients. Slomowitz et al 30 have reported that some patients cannot maintain protein balance and lack of uremic toxicity with an energy intake of 25 to 35 kcal/kg/day and protein intake of 1.1 g/kg/day, requiring a slightly greater protein intake of 1.2 g/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, tem sido sugerido que em pacientes em hemodiálise a retenção de nitrogênio é dependente da ingestão energética. Uma ingestão energética insuficiente leva a um balanço nitrogenado negativo, ainda que na vigência de uma oferta protéica adequada, enquanto que uma oferta elevada de energia aumenta a utilização protéica, proporcionando um balanço nitrogenado neutro a positivo 32 .…”
unclassified